Linear cellular automata: Garden of Eden Theorem, L-surjunctivity and group rings - Ceccherini-Silberstein, T.; Coornaert, M. (Algebra and Discrete Mathematics, 2006)
This paper is a slightly extended version of the lecture given by the first author at the “5th International Algebraic Conference in Ukraine” held on July 20–27 2005 at the Odessa I.I. Mechnikov National University.